Manajemen Kepala Sekolah dalam Meningkatkan Kompetensi Guru Di SMA Muhammadiyah 3 Jember - AFIFAH, YAUMUL; , Prof. Dr. Bambang Sumardjoko; , Prof. Dr. Endang Fauziati, M. Hum (2016)
This research shows the problem about the management of school principal in planning, organizing, actuating and controlling the teachers' performance so that their competences (especially pedagogical and professional competence) more to developed. The purpose of this research is getting the description about planning, organizing, actuating and controlling by the principal to improve the teachers' competences at Muhammadiyan Senior High School 3 Jember. This research use qualitative method by describing the model of principal's management in improving pedagogical and professional competences of the teachers. The result of this research reveals that the principal's planning in improving teachers' competences consist of 1) the arrangement of component and management in Teaching and Learning program 2) the teachers' placement to the appropriate classes based on their capabilities. 3) the Computer Information Technology training and Peer teaching, and also 4) recruitment and counseling to the new teachers. The Principal's organizing in improving teachers' competence consist of 1) the management of customers satisfaction questionnaire 2) the management of training and supervision application 3) the management of Human resource development. The Principal's applications in improving teachers' competences consist of 1) the principal's cooperation with stakeholders, 2) the management of students learning problems 3) supporting the teachers in professional development study. About the Principal's supervisions, they consist of 1) the supervision of teachers and students activities 2) the supervision of teachers' performances 3) the monitoring of training and peer teaching, and 4) the monitoring of teachers' study permission.